Low-cycle fatigue fracture in metallic alloy materials with mutiple internal cracks - Chen, Yali (Nanyang Technological University, 2021)
For failure analysis and prevention of various engineering materials and structures, the advanced finite element method (XFEM) and cohesive force (Cohesive) model have been widely used to simulate the random cracks in those materials and structures. In the current project, the cohesion model is used to simulate the propagation of a random crack in metallic alloy materials. In order to analyze the influence of inclusions (embedded in those materials) and their material properties on the crack propagation path, the propagation of the crack in the symmetrical inclusion region is simulated. The situation of a crack penetrating into or bypassing an inclusion in certain cases has been simulated and analyzed.